PENGEMBANGAN EKONOMI PERBATASAN BERBASIS PENGUATAN BADAN USAHA MILIK DESA STUDI PADA KECAMATAN SAMBAS - Sumar’in Sumar’in (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Sambas Regency is one of the districts in West Kalimantan Province, directly adjacent to the state of Sarawak, Malaysia. As a Border Area, Sambas Regency need a model of economic development that is oriented towards community empowerment and local potential. The potential development of Sambas Sub district should start from the Village with make BUMDesa. It is hoped that the presence of the Village autonomy mechanism will make the village more creative and innovative. Because BUM Desa Is business Institutional from village community. This research uses field research and is a case study. The conclusion this research show the potential BUM Desa in Sambas include The amount of support from the village government in the effort to establish BUM Desa, The size of the economic potential of the village and Central and regional government policies in encouraging the progress of the village.